ROUNDTABLE AND THINK PAIR SHARE COMBINED WITH PICTURE AS MEDIA IN TEACHING WRITING OF DESCRIPTIVE TEXT - Fajlin, Eka Yulianti; Pratama, Hendi (ELT Forum: Journal of English Language Teaching, 2018)
Writing is one of the skills which is difficult to be mastered by students since it requires a higher level of productive language control than other skills. Therefore, in teaching writing teachers should have a creative way to make students learn writing easily. This study was concerned with the implementation of Roundtable and Think Pair Share combined with picture in teaching writing of descriptive text. The aims of this study: (1) to find out the effective techniques between Roundtable and Think Pair Share combined with picture as media, (2) to know studentsâ perception about those techniques. The data collection techniques used tests and questionnaire. The pre-test result in experimental group 1 and 2 were 60.86 and 60.69. The post-test result in experimental group 1 and 2 were 84.89 and 75.51. T-test post-test showed that Sig. (2-tailed) was 0.001 and t-test was 7.932. The test result showed significant improvement of studentsâ writing achievement in both group.Therefore, both techniques combined with picture were effective to teach writing of descriptive text. However, there was a significant difference between post-test scores in both group. It could be concluded that Roundtable combined with picture was more effective than Think Pair Share combined with picture in teaching writing of descriptive text. The questionnaire results showed both techniques combined with picture were interesting, some students in experimental group 1 got difficulty whereas many students in experimental group 2 got difficulty in writing, the learning process using both techniques were effective, and both techniques could be  used in another meeting.